Heterogeneity of carbon loss and its temperature sensitivity in East-European subarctic tundra soils - Diáková, Kateřina; Čapek, Petr; Kohoutová, Iva; Mpamah, Promise A; Bárta, Jiří; Biasi, Christina; Martikainen, Pertti J; Šantrůčková, Hana (FEMS microbiology ecology, 2016)
Arctic peatlands store large stocks of organic carbon which are vulnerable to the climate change but their fate is uncertain. There is increasing evidence that a part of it will be lost as a result of faster microbial mineralization. We studied the vulnerability of 3500-5900 years old bare peat uplifted from permafrost layers by cryogenic processes to the surface of an arctic peat plateau. We aimed to find biotic and abiotic drivers of CLOSS from old peat and compare them with those of adjacent, young vegetated soils of the peat plateau and mineral tundra. The soils were incubated in laboratory at three temperatures (4°C, 12°C and 20°C) and two oxygen levels (aerobic, anaerobic). CLOSS was monitored and soil parameters (organic carbon quality, nutrient availability, microbial activity, biomass and stoichiometry, and extracellular oxidative and hydrolytic enzyme pools) were determined. We found that CLOSS from the old peat was constrained by low microbial biomass representing only 0.22% of organic carbon. CLOSS was only slightly reduced by the absence of oxygen and exponentially increased with temperature, showing the same temperature sensitivity under both aerobic and anaerobic conditions. We conclude that carbon in the old bare peat is stabilized by a combination of physical, chemical and biological controls including soil compaction, organic carbon quality, low microbial biomass and the absence of plants.
Keywords: Arktida; Permafrost; laboratory incubation; Temperature; soil carbon loss; Tundra; teplota; půda; biomasa; arctic peatlands; tundra; Carbon; půdní mikrobiologie; Arctic Regions; oxygen; Soil; Biomass; uhlík; microbial biomass; permafrost; temperature; Soil Microbiology